DEVELOPING A MODEL OF A SUSTAINABLE MICRO HYDROPOWER PLANT MANAGEMENT SYSTEM (A CASE STUDY KEDUNGRONG MHP PURWOHARJO VILLAGE SAMIGALUH DISTRICT KULON PROGO REGENCY YOGYAKARTA PROVINCE) - Aspita Dyah Fajarsari; Muhammad Sulaiman; Bakti Setiawan (ASEAN Journal of Systems Engineering, 2015)
Yogyakarta Province until 2014 has built a total of 10 (ten) micro hydropower plants (MHP). However, from these ten MHPs, there is only 1 (one) which is still in operation, namely Kedungrong MHP. This Kedungrong MHP was selected as the research area due to its success in managing the MHP so that the electricity generated can be used by its local residents until now. Based on this best practice, the other MHPs which are still under construction or that have ‘stalled’ should learn from Kedungrong MHP to be able to reoperate so that they will be sustainable.This research employed mixed methods, between the quantitative research method and the qualitative research method. First, the data were collected using surveys, interviews and observation and then the model of the management system that Kedungrong MHP applies was described and evaluated.The findings of the research suggest that a sustainable MHP integrates three aspects, namely technical and environmental, social as well as economic aspects. The technical aspects deals with civil, mechanical and electrical components at the stages of planning, developing to operation and maintenance. The social aspects look carefully at community participation at the stages of planning, developing to operation and maintenance. Finally, the economic aspects pay attention to sources and forms of financing at the investment stage, the operation stage and the maintenance stage. In relation to the MHP scale, of those three aspects, the one that has the most significant impact on the sustainability of the MHP is the social aspects.